Exosomal microRNA miR-92a concentration in serum reflects human brown fat activity - Chen, Yong; Buyel, Joschka J.; Hanssen, Mark J. W.; Siegel, Franziska; Pan, Ruping; Naumann, Jennifer; Schell, Michael; van der Lans, Anouk; Schlein, Christian; Froehlich, Holger; Heeren, Joerg; Virtanen, Kirsi A.; et al. (Nature communications, 2016)
Brown adipose tissue (BAT) dissipates energy and its activity correlates with leanness in human adults. 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography coupled with computer tomography (PET/CT) is still the standard for measuring BAT activity, but exposes subjects to ionizing radiation. To study BAT function in large human cohorts, novel diagnostic tools are needed. Here we show that brown adipocytes release exosomes and that BAT activation increases exosome release. Profiling miRNAs in exosomes released from brown adipocytes, and in exosomes isolated from mouse serum, we show that levels of miRNAs change after BAT activation in vitro and in vivo . One of these exosomal miRNAs, miR-92a, is also present in human serum exosomes. Importantly, serum concentrations of exosomal miR-92a inversely correlate with human BAT activity measured by 18 F-FDG PET/CT in two unique and independent cohorts comprising 41 healthy individuals. Thus, exosomal miR-92a represents a potential serum biomarker for BAT activity in mice and humans. Exosomes are RNA-containing lipid vesicles with roles in inter-tissue crosstalk. Here the authors show that exosome release from brown adipocytes is increased upon thermogenic activation, both in vitro and in vivo , and demonstrate that serum levels of exosomal miR-92 reflect brown fat activity in humans.